PENYELESAIAN SENGKETA PENYEROBOTAN NAMA DOMAI(CYBERSQUATING): STUDI KASUS SONY ARIANTO KURNIAWAN (SONY A.K.) VS SONY CORP. (JEPANG) - Sri Wasiyanti (Cakrawala - Jurnal Humaniora, 2011)
The rise of Internet usage has penetrated into all aspects of life. There was no denying that somany of the benefits gained from internet presence. Use of the Internet not only to find the desiredinformation but has already become a new trend to hold a sale and purchase transactions online,or better known as e-commerce. The number of addresses contained in this Internet site led to apossible violation of these sites, such as hacking case against a particular site is not a noveltyanymore. But the case of annexation there are also domain name or Web sites known by certainparties with a purpose that is known by the public using the internet media so that people willassume that the site is the original site of a trademark. This is one violation that must be resolvedon the basis of governance regulations in Indonesia, even if the site is owned by another countrythen the dispute should be resolved by legislation and international law.Keywords: Cybersquating, Dispute